THE PATTERN OF UNDERGRADUATE THESIS BACKGROUND RHETORIC OF TWO UNIVERSITIES IN ACEH - Imam Al Farisyi; Iskandar Abdul Samad; Saiful Marhaban (Premise: Journal of English Education and Applied Linguistics, 2022)
This research examined the rhetorical pattern of thesis background, particularly the undergraduate scripts of English education department students. The purpose of the study is to find out the tendency of rhetorical patterns by students in writing thesis backgrounds.  The approach used in this study is a qualitative method. The researcher investigates twenty English education undergraduate scripts from UIN Ar-Raniry and Syiah Kuala University. To collect the data, documentation of undergraduate thesis background was used as the instrument. The data were collected   from the electronic   repository   thesis  and  dissertation   from  both universities.  Then, the researcher examined the data based on the framework  of Swales’s CARS model (2004). The results of this research revealed that the undergraduate  students of English departments have similar rhetorical patterns in the thesis background. Furthermore, the research identified the cyclical pattern which showed that the students tend to repeat the cycle. Students tend to use the first language style that led the students to write circumstantially to deliver their points in the thesis background.  In conclusion,  the rhetorical  pattern of the thesis background used by students is compatible with the theoretical framework. Bearing the problems in mind, this research has implication on the students majoring in English Education to employ more effective rhetorical patterns in the background of undergraduate scripts crafted in English.